Association between BMI and semen quality: an observational study of 3966 sperm donors. Issue 1 (8th November 2018) - Ma, Jixuan; Wu, Li; Zhou, Yun; Zhang, Hai; Xiong, Chengliang; Peng, Zhe; Bao, Wei; Meng, Tianqing; Liu, Yuewei
Abstract: STUDY QUESTION: What is the relationship between abnormal BMI and semen quality? SUMMARY ANSWER: Underweight was significantly associated with lower sperm concentration, total sperm number and total motile sperm count, while overweight was significantly associated with lower semen volume, total sperm number and total motile sperm count. WHAT IS KNOWN ALREADY: Abnormal BMI has been associated with lower semen quality, but the results remain somewhat controversial. In addition, most previous studies have focused on the influence of obesity or overweight on semen quality, and evidence on the association between underweight and semen quality is rare. STUDY DESIGN, SIZE, DURATION: This research was an observational study investigating 3966 sperm donors from a large sperm bank in Wuhan city, China. These donors passed the screening for sperm donation and underwent 29 949 semen examinations between 1 January 2013 and 9 April 2018. PARTICIPANTS/MATERIALS, SETTING, METHODS: BMI was categorized into four groups: underweight (<18.5 kg/m 2 ), normal weight (18.5–24.9 kg/m 2 ), overweight (25–29.9 kg/m 2 ) and obese (≥30 kg/m 2 ). Semen volume, sperm concentration, total sperm number, total motility, progressive motility and total motile sperm count were determined by trained clinical technicians. Linear mixed models were used to conduct dose–response analyses between BMI and semen quality parameters. MAIN RESULTS AND THE ROLE OF CHANCE: Underweight was significantly associated with a 3.0% (95% CI: 0.1%, 5.8%), 6.7% (1.9%, 11.3%) and 7.4% (2.2%, 12.4%) reduction in sperm concentration, total sperm number and total motile sperm count, respectively. Overweight was significantly associated with a 4.2% (1.6%, 6.8%), 3.9% (0.9%, 6.9%) and 3.6% (0.2%, 6.9%) reduction in semen volume, total sperm number and total motile sperm count, respectively. Non-linear models including continuous BMI as a natural cubic spline function yielded similar results. LIMITATIONS, REASONS FOR CAUTION: Our study subjects were sperm donors who are typically young and healthy, and therefore not representative of the general male population. Caution should be paid in generalizing our results to other populations. Furthermore, we did not measure the donors' weight repeatedly along with each semen donation; instead, we only measured it once during the screening, which may cause bias due to the variations of weight across time. WIDER IMPLICATIONS OF THE FINDINGS: Our study provides evidence that underweight and overweight are associated with lower semen quality, and highlights the importance of maintaining a normal weight for men. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the Health and Family Planning Commission of Hubei Province (Grant number WJ2015MA027), the Hubei Provincial Committee of the Communist Youth League of China, and Center for Global and Regional Environmental Research at the University of Iowa. The authors declare that there are no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.